To simplify \(4^3 \times 4^6\), we can use the property of exponents that states \(a^m \times a^n = a^{m+n}\).
Applying this property:
\[ 4^3 \times 4^6 = 4^{3+6} = 4^9 \]
Thus, the simplified expression is:
\[ \boxed{4^9} \]
4, cubed, times, 4, to the power 6
4
3
×4
6
1 answer
To simplify \(4^3 \times 4^6\), we can use the property of exponents that states \(a^m \times a^n = a^{m+n}\).
Applying this property:
\[ 4^3 \times 4^6 = 4^{3+6} = 4^9 \]
Thus, the simplified expression is:
\[ \boxed{4^9} \]